Localizing selected endocytosis protein candidates in Plasmodium falciparum using GFP-tagged fusion constructs - Basson, Travis (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
Malaria is a mosquito-borne infectious disease caused by several obligate intracellular protozoan parasites in the Plasmodium genus, with Plasmodium falciparum causing the most widespread cases and malaria deaths. In 2013 there were approximately 190 million cases of the disease and between 584,000 and 855,000 deaths. It is essential to identify novel drug targets and develop novel drug candidates due to the increase in resistance of P. falciparum parasites to the current arsenal of antimalarial drugs. Endocytosis is an essential process in eukaryotic cells in which the external environment is internalized by the cell in order to obtain various particles from the extracellular space. This extracellular cytoplasm is internalized in membrane-bound invaginations at the plasma membrane. During the blood stage of malaria infection, the parasite requires nutrients from the host red blood cell. To obtain these nutrients, the parasite internalizes haemoglobin in large amounts and degrades it in an acidic, lysosome-like organelle, known as the digestive vacuole. Whilst the exact molecular mechanism of malaria parasite endocytosis is not yet fully understood, a number of proteins have been suggested to be involved. The most expedient approach in identifying candidate endocytosis proteins is to investigate parasite homologues of proteins known to be involved in endocytosis in mammalian cells. The three proteins selected for investigation in this study were the P. falciparum homologues of coronin, dynamin 2, and Î¼4. The coding sequences for the candidate endocytosis proteins were amplified by PCR and cloned into the pARL2-GFP expression vector. P. falciparum 3D7 parasites were transfected with these vectors and the episomal expression of full-length GFP-tagged fusion protein was confirmed by Western blot analysis using commercially available anti-GFP antibodies. Microscopic analysis of live parasites using fluorescence and confocal microscopy was used to determine the localization of the candidate endocytosis proteins. Coronin appeared to display diffuse cytoplasmic GFP localization during the trophozoite stage, arguing against a role in endocytosis. However, distinct localization during the schizont stage at what appears to be the inner membrane complex was observed. Coronin is thus likely required to coordinate the formation of the actin network between the merozoite IMC and the plasma membrane on which the glideosome is dependant for generating the motile forces required for the merozoite motility and invasion of RBCs. Dynamin 2 displayed localization at three potential locii: the parasite periphery (plasma membrane), punctuate regions within the cytoplasm (potentially at membrane bound organelles) and at the parasite food vacuole. The data suggested that dynamin 2 is involved in endocytosis and membrane trafficking in a similar manner to classical dynamins, potentially as a vesicle scission molecule at the plasma membrane, mediating vesicle formation at the food vacuole to recycle membrane to the plasma membrane, and possibly mitochondria organelle division. Î¼4 displayed transient localization, cycling between cytosolic localization, and localization to distinct regions at the plasma membrane and the food vacuole. Localization of PfÎ¼4 to the plasma membrane is indicative of a role for Î¼4 as a part of an adaptor protein (AP) complex which may be responsible for recruitment of clathrin to initiate endocytosis in a manner similar to mammalian AP-2. As was observed with PfDYN2, PfÎ¼4 localizes to the FV, which suggests that PfÎ¼4 forms part of a coat complex that mediates the formation of vesicles that recycle membrane from the FV to the parasite plasma membrane. This study showed that expressing proteins as full-length GFP-tagged fusion constructs is an effective approach in the early stages of determining the localization and function of P. falciparum proteins in vitro, and distinguishing between candidates that have a potential role in endocytosis and those that are unlikely to do so.
Keywords: Uncatalogued